The response of plants and crops of white Pumpkins (Legeneria leucantha) Manisa Variety, un the provision cow manure and NPK Pearls fertilizer - Wiwinata, Dwita; Sujalu, Akas Pinaringan (Universitas 17 Agustus 1945 Samarinda, 2018)
Objective of the study is to determinate the effect of cow manure and NPK Pearls fertilizer and their interaction on the growth and yield of white pumpkin (Legeneria leucantha) Manisa variety. The research was conducted from March 2016 t0 June 2016, in Segoy Makmur, Sub Districd Long Mesangat, Wesh kutai Regency, East Kalimantan Province.The study design used a 4x4 factorial experiment in a Completely Randomized Group (CRG), and repeated 4 times. The first factor is the cow manure (K), consisting of four levels namely ; no cow manure fertilizer application (k0), dose 5 ton ha-1 equivalent to 50 g/plants-1 (k1), dose 10 ton ha-1 equivalent to 100 g/plants-1 (k2), dose 15 ton ha-1 equivalent to 150 g/plants-1 (k3). The second factorial is the application of NPK Pearls fertilizer (N), consisting of four levels namely ; no NPK Pearls fertilizer application (k0), dose 200 kg/ha-1 equivalent to 2,00 g/plant-1 (n1), dose 300 kg/ha-1 equivalent to 3,00 g/plant-1 (n2), dose 400 kg/ha-1 equivalent to 4,00 g/plant-1 (n3).Manure application not significant on plant height, aged 20, 40, and 60 days after planting, and significantly different to the age of the plant at planting, but highly significant of the life of the current crop of fruit, fruit number and weight of the fruit crop planting. Reseach results show that the treatment, NPK pearl very, significant effect of plant height at 20, 40, and 60 days after planting, and no real effect on the age of the plant during flowering, fruiting age of the of the current crop, planting fruit number and weight of the fruit crop. Application between cow manure and fertilizers NPK pearl effect no significant effect on plant height at 20, 40, and 60 days after planting during flowering, the age of the current per plant, and weight of fruit per plant.